In Silico Evaluation of the Antibacterial and Antiviral Potential of Nusbiarylin Derivatives - Milić, Ognjen; Nedeljković, Nikola; Nikolić, Miloš (Archives of Pharmacy, 2026)
Antimicrobial resistance and chronic viral infections are major challenges in contemporary medicine. This in silico study evaluated the dual inhibitory potential of 16 designed nusbiarylin derivatives against two clinically relevant enzymatic targets: Escherichia coli (E. coli) RNA polymerase (RNAP) and hepatitis C virus RNA-dependent RNA polymerase (HCV RNAP). Semi-flexible molecular docking was performed using AutoDock Vina. Six compounds – 5, 6, 7, 8, 15, and 16 – showed the most favorable dual inhibitory potential, forming key hydrogen bonds with Ser642 of E. coli RNAP and with Tyr477 and Arg422 of HCV RNAP, along with significant hydrophobic interactions. The presence of cyano or nitroso groups as hydrogen bond acceptors, and sulfonyl or sulfoxide groups contributing π-S interactions, were identified as key determinants of binding affinity at both targets. These findings support further experimental evaluation of nusbiarylin derivatives as potential dual-activity antibacterial and antiviral agents.
Keywords: molecular docking; nusbiarylin derivatives; drug-likeness analysis; RNA polymerase; HCV RNAP; dual inhibitors